Challenges Faced by Children and Adults in Learning English as a Second Language - Berliana Salsabila; Lusiana Suciati Dewi (Teaching English and Language Learning English Journal, 2026)
Learning English has become increasingly important in the global era, particularly in educational and professional contexts. However, learners of different ages often experience distinct challenges in acquiring English. This study aims to identify and compare the challenges faced by children and adult learners in learning English. This study employed a qualitative approach using semi-structured interviews with four participants consisting of two children and two adult learners. The data were analyzed using thematic analysis to identify key themes related to linguistic, psychological, behavioral, and environmental challenges. The findings reveal that children mainly experience difficulties in vocabulary and speaking, along with feelings of shyness and nervousness. In contrast, adult learners face more complex challenges, particularly in grammar and pronunciation, as well as higher levels of anxiety and lack of confidence. Additionally, children tend to rely on classroom learning, while adult learners demonstrate more autonomous learning through various media. Environmental factors also influence both groups, with children having limited exposure and adults having more opportunities but still facing psychological barriers. In conclusion, age differences significantly affect the challenges in learning English, suggesting the need for age-appropriate teaching strategies to improve language learning outcomes.